THEORETICAL APPROACHES TO PARTY MEMBERSHIP AND ORGANIZATIONAL STRUCTURE OF POLITICAL PARTIES - Maciel, Tito Lívio Cabral Renovato Silva (2023)
The aim of this chapter is to describe some theoretical contributions in the literature on party membership as a “dependent variable” of party organization. According to Scarrow (2000), measuring the number of members is a way of verifying the nature of the organizational links between parties and their members. Since this paper starts from an organizational approach to political parties, this first chapter briefly presents the following theoretical aspects a) the definitions of “party membership” and “political party” used in this work; b) the main theoretical contributions on party organization, with emphasis on the main typologies of political parties present in the literature; c) studies on the decline of party membership in Europe and their respective conclusions; d) the theoretical model of Panebianco (2005), which brings categories from the theory of complex organizations to the literature on party organizations.